Effect of Negative Ion Concentration and Magnetic Field on Electronegative Plasma Sheath - Chalise, Roshan; Nepali, Bhujendra; Thakur, Ghanshyam; Basnet , Suresh; Khanal , Raju (Tribhuvan University Journal, 2021)
Plasma is the ionized state of matter and is of interest as it has found applications in diverse fields. In all practical applications of plasma, it interacts with the material surface via non-neutral region that is formed between bulk plasma and surface known as the sheath, which plays a vital role in overall plasma properties. In this work, the characteristics of electronegative magnetized plasma sheath have been presented employing the kinetic trajectory simulation method based on kinetic theory. It is found that magnetic field and volumetric composition of negatively charged particles have significantly affected the characteristics of electronegative plasma sheath. Although the particle densities deplete towards the wall, the decreasing rate of negative charged particles is steeper than that of positive ions. The magnitude of electric field slowly increases close to the sheath entrance, whereas it sharply increases close to the wall. The positive ion density decreases in both cases when the concentration of negative ion is increased or when the magnetic field is increased. On increasing the magnetic field from 0 to 250 mT, the ion density reaching the wall decreases from 0.331 to 0.305 n ps. The results are similar and agree with similar works following different models and our model provides a satisfactory basis for the study of electronegative plasma sheath.